Telomeres, the loop tying cancer to organismal life‐histories. Issue 23 (20th May 2022) - Ujvari, Beata; Raven, Nynke; Madsen, Thomas; Klaassen, Marcel; Dujon, Antoine M.; Schultz, Aaron G.; Nunney, Leonard; Lemaître, Jean‐François; Giraudeau, Mathieu; Thomas, Frédéric
Abstract: Recent developments in telomere and cancer evolutionary ecology demonstrate a very complex relationship between the need of tissue repair and controlling the emergence of abnormally proliferating cells. The trade‐off is balanced by natural and sexual selection and mediated via both intrinsic and environmental factors. Here, we explore the effects of telomere‐cancer dynamics on life history traits and strategies as well as on the cumulative effects of genetic and environmental factors. We show that telomere‐cancer dynamics constitute an incredibly complex and multifaceted process. From research to date, it appears that the relationship between telomere length and cancer risk is likely nonlinear with good evidence that both (too) long and (too) short telomeres can be associated with increased cancer risk. The ability and propensity of organisms to respond to the interplay of telomere dynamics and oncogenic processes, depends on the combination of its tissue environments, life history strategies, environmental challenges (i.e., extreme climatic conditions), pressure by predators and pollution, as well as its evolutionary history. Consequently, precise interpretation of telomere‐cancer dynamics requires integrative and multidisciplinary approaches. Finally, incorporating information on telomere dynamics and the expression of tumour suppressor genes and oncogenes could potentially provide the synergistic overview that could lay the foundations to study telomere‐cancer dynamics at ecosystem levels.